THE REACTION OF DEHYDROHALOGINATION OF 1,1,2-TRICHLOROETHANE ON A GETEROGENIOUS CATALYST - Білокопитов, Ю. В.; Драч, О. М.; Вдовин, В. С.; Огданська, О. О.; Чернобаєв, И.И. (Science-based technologies, 2009)
The reaction of dehydrohalogination of 1,1,2-trichloroethane on a geterogenious catalyst was investigated. It was shown, that selectivity after vinylidenchloride grows with the increase of basis of surface of catalyst.